The adventures of the dish and the spoon - Grey, Mini. (New York : Knopf, 2006)
Having run away together, the Dish and the Spoon from the nursery rhyme "The Cat and the Fiddle" become vaudeville stars before turning to a life of crime.
Horn Book Starred.
Notable/Best Books (A.L.A.).
School Library Journal.
2.3
K-3
Keywords: Characters and characteristics in literature -- Juvenile fiction; Spoons -- Juvenile fiction; Tableware -- Juvenile fiction; Characters in literature -- Fiction; Humorous stories; Spoons -- Fiction; Tableware -- Fiction; Characters and characteristics in literature -- Fiction; Humorous fiction; Spoons -- Fiction; Tableware -- Fiction; Humorous fiction